Ohlin and Levin-Stečkin-type results for strongly convex functions - Nikodem, Kazimierz; Rajba, Teresa (Annales Mathematicae Silesianae, 2020)
Counterparts of the Ohlin and Levin–Stečkin theorems for strongly convex functions are proved. An application of these results to obtain some known inequalities related with strongly convex functions in an alternative and unified way is presented.